Prevention of childhood obesity and food policies in Latin America: from research to practice. (July 2017) - Pérez‐Escamilla, R.; Lutter, C.K.; Rabadan‐Diehl, C.; Rubinstein, A.; Calvillo, A.; Corvalán, C.; Batis, C.; Jacoby, E.; Vorkoper, S.; Kline, L.; Ewart‐Pierce, E.; Rivera, J.A.
Summary: Background: Addressing childhood obesity in Latin America requires a package of multisectoral, evidence‐based policies that enable environments conducive to healthy lifestyles. Objective: Identify and examine key elements to translating research into effective obesity policies in Latin America. Methods: We examined obesity prevention policies through case studies developed with an expert in the specific policy. Policies were selected based on their level of implementation, visibility and potential impact to reduce childhood obesity. They include: (i) excise taxes on sugar sweetened beverages and energy‐dense foods; (ii) front‐of‐package food label legislation; (iii) trans fatty acids removal from processed foods; and (iv) Ciclovías recreativas or 'open streets'. Case studies were coded to identify components that explained successful implementation and sustainability using the Complex Adaptive Health Systems framework. Results: The analysis identified key elements for effective and sustainable policy, including evidence justifying policy; evidence‐based advocacy by civil society; political will; and legislation and skillful negotiations across government, academia, the private sector and civil society. Scientific evidence and evaluation played an important role in achieving tipping points for policies' launch and sustain effective implementation. Conclusions: Well‐coordinated, intersectoral partnerships are needed to successfully implement evidence‐based anti‐obesity policies. Prospective policy research may be useful for advancing knowledge translation.